Síndrome de Burnout em trabalhadores de um serviço público de saúde do município de Serra-ES - Santos, Claudia Roberta (2009)
Burnout has been seen as a reaction to the chronic emotional strain of dealing too much with people. It is a syndrome comprising by three dimensions related but independent: the emotional exhaustion, which is characterized by lack of energy and enthusiasm, depersonalization, which is characterized by the development of an emotional insensitivity, and reduction of personal fulfillment at work, which is characterized by tendency of workers to self assess themselves in a negative way (CARLOTTO; PALAZZO, 2006). This study aimed to characterize the sociodemographic profile and labor of health workers at Pronto Atendimento Adulto, Infantil and Maternidade Municipal of Carapina (Ready Adult Care, Child and Parenting Municipal Carapina) in the municipality of Serra-ES; to identify the occurrence of symptomatology related to Burnout Syndrome (BS) and relate it to the sociodemographic aspects, labor and workers. It is a descriptive study with quantitative approach, conducted with a population consisting of 164 health professionals (57 doctors, 20 nurses and 87 nursing assistants and technicians) in the period from September 1 to November 30, 2008. To characterize the profile of health workers of sites studied it was used a questionnaire that collected data on socio-demographics aspects, work situation, the worker characteristics and sources of tension and fatigue. The occurrence of symptomatology related to Burnout Syndrome among Health Workers was identified using the MBI (Malasch Burnout Inventory-HSS) and to relate the occurrence of symptomatology with the profile of workers were bivariate analysis was performed with the dependent variable symptomatology of Burnout and the other independent variables. The appearance of symptomatology of the syndrome showed the average index of 2,68 for the dimension Emotional Exhaustion (EE), the low rate of 2,09 for the Depersonalization Scale (DS) and low index of 1,13 for the small Professional Achievement (PA). Probably, the occurrence of symptomatology related to Burnout Syndrome in health workers studied is not higher because of proportionally large personal fulfillment at work (3,87). Were associated with three dimensions of the BS: pay less income, difficulty in repairing sleep after work shift, sleepiness at work and issues related to lack of personal control over the work's organization, leading to dissatisfaction of the users served. The elaboration of public policies is required to face new problems and the impossibility to resolve them. The emergence of BS as a health problem, still incipient in the health of the worker, the ignorance by the majority of health professionals about the syndrome and the naturalization of female predominance in health demonstrate the need for public policy proposals, and research also giving consideration to spread, credit, make scientific and build a theoretical contribution toward the Brazilian reality.